Tracing monadic computations and representing effects - Pirog, M; Gibbons, J (Open Publishing Association, 2012)
In functional programming, monads are supposed to encapsulate computations, effectfully producing the final result, but keeping the means of acquiring it to themselves. For various reasons, we sometimes want to reveal the internals of a computation. To make that possible, in this paper we introduce monad transformers that add the ability to automatically accumulate observations about the course of execution as an effect. We discover that if we treat the resulting trace as the actual result of the computation, we can find new functionality in existing monads, notably when working with non-terminating computations.